Implementasi Excellence Public Relations dan Coordinated Management of Meaning pada Sosialisasi Empat Pilar Utama SABar School, Banyumas - Turistiati, Ade Tuti; Nan Kinasih, Eyora Jasmine; Nurcandrani, Prita Suci (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
SABar School (Sekolah Alam Baturraden) applies four main pillars namely the pillars of morals, logic, leadership, and entrepreneurship in the student learning process. However, the view of the Banyumas community is that SABar School is only a school that involves more playing than learning activities. Parents are worried that sending their children to SABar School will be left behind in academics. This research aims to analyze the implementation of excellence in public relations and coordinated management of meaning towards the socialization of the four main pillars of SABar School. This research uses a qualitative descriptive research method with data collection techniques of observation and in-depth interviews with ten informants, supported by secondary data through literature studies. The research shows that SABar School's role in socializing activities on the four main pillars implements eight of the ten premises of public relations excellence. Two premises that have not been implemented are the integration premise because SABar School does not yet have a dedicated PR division and the independence premise. The management function of PR is still one with other management. Meanwhile, the results of coordinated management of meaning on the four main pillars show that SABar School has achieved a level of coordination.